Ecosystem Engineers in a Self-organized Soil: A Review of Concepts and Future Research Questions. Issue 3 (March 2016) - Lavelle, Patrick; Spain, Alister; Blouin, Manuel; Brown, George; Decaëns, Thibaud; Grimaldi, Michel; Jiménez, Juan José; McKey, Doyle; Mathieu, Jérôme; Velasquez, Elena; Zangerlé, Anne
Abstract : Abstract: Soils are self-organized ecological systems within which organisms interact within a nested suite of discrete scales. Microorganisms form communities and physical structures at the smallest scale (microns), followed by the community of their predators organized in microfoodwebs (tens of microns), the functional domains built by ecosystem engineers (centimeters to meters), ecosystems, and landscapes. Ecosystem engineers, principally plant roots, earthworms, termites, and ants, play key roles in creating habitats for other organisms and controlling their activities through physical and biochemical processes. The biogenic, organic, and organomineral structures that they produce accumulate in the soil space to form three-dimensional mosaics of functional domains, inhabited by specific communities of smaller organisms (microfauna and mesofauna, microorganisms) that drive soil processes through specific pathways. Ecosystem engineers also produce signaling and energy-rich molecules that act as ecological mediators of biological engineering processes. Energy-rich ecological mediators may selectively activate microbial populations and trigger priming effects, resulting in the degradation, synthesis, and sequestration of specific organic substrates. Signaling molecules inform soil organisms of their producers' respective presences and change physiologies by modifying gene expression and through eliciting hormonal responses. Protection of plants against pests and diseases is largely achieved via these processes. At the highest scales, the delivery of ecosystem services emerges through the functioning of self-organized systems nested within each other. The integrity of the different subsystems at each scale and the quality of their interconnections are a precondition for an optimum and sustainable delivery of ecosystem services. Lastly, we present seven general research questions whose resolution will provide a firmer base for the proposed conceptual framework while offering new insights for sustainable use of the soil resource.